Indoor particulate pollution in fitness centres with emphasis on ultrafine particles - Slezakova, Klara (2020)
Fitness centres (FC) represent a unique indoor microenvironment. Exercising on regular basis provides countless health benefits and improves overall well-being, but if these facilities have poor indoor air quality, the respective exercisers might be subjected to some adverse risks. Considering the limited existent data, this work aimed to evaluate particulate pollution (PM10, PM2.5, and ultrafine particles - UFP) in indoor air of FC and to estimate the respective risks for occupants (both staff and exercising subjects). Sampling was conducted during 40 consecutive days of May-June 2014 in general fitness areas, studios and classrooms (for group activities) of four different fitness centres (FC1-FC4) situated within Oporto metropolitan area, Portugal. The results showed that across the four FC, PM10 ranged between 5 and 1080 μg m-3 with median concentrations (15-43 μg m-3) fulfilling the limit (50 μg m-3) of Portuguese legislation in all FC. PM2.5 (medians 5-37 μg m-3; range 5-777 μg m-3) exceeded thresholds of 25 μg m-3 at some FC, indicating potential risks for the respective occupants; naturally ventilated FC exhibited significantly higher PM ranges (p < 0.05). Similarly, UFPs (range 0.5-88.6 × 103 # cm-3) median concentrations were higher (2-3 times) at FC without controlled ventilation systems. UFP were approximately twice higher (p < 0.05) during the occupied periods (mean of 9.7 × 103vs. 4.8 × 103 # cm-3) with larger temporal variations of UFP levels observed in general fitness areas than in classrooms and studios. Cardio activities (conducted in studios and classrooms) led to approximately twice the UFPs intakes than other types of exercising. These results indicate that even short-term physical activity (or more specifically its intensity) might strongly influence the daily inhalation dose. Finally, women exhibited 1.2 times higher UFPs intake than men thus suggesting the need for future gender-specific studies assessing UFP exposure.